Challenges and Opportunities in Implementing Sharia Principles in Business Management - Talib, Ahmad; Paturochman, Iwan Ridwan; Ansyori, Ahmad; Al-Amin, Al-Amin (Sharia Business Management Department of STEBIS Bina Mandiri, 2024)
The integration of Sharia principles into business management represents a burgeoning field of interest in both academic and practical realms. This paper delves into the multifaceted challenges and opportunities encountered in aligning business operations with Sharia mandates. Sharia, grounded in ethical imperatives, seeks to promote justice, transparency, and social welfare when applied to business practices. While the integration of Sharia principles is observed across Islamic economies and increasingly within Western contexts, challenges abound. These include regulatory barriers, market competition, lack of awareness, and interpretation difficulties, all requiring serious attention for successful implementation. Despite these challenges, embracing Sharia principles unveils substantial opportunities. It opens avenues for tapping into Islamic finance markets, enhances brand loyalty, and fosters improved stakeholder relationships. Moreover, it contributes to societal well-being by promoting ethical behavior and social responsibility. A comparative analysis, whether empirical or through literature review, offers insights into the effectiveness and acceptance of Sharia compliance in business management, guiding strategic decision-making for organizations seeking to blend profitability with ethical principles.